[Race Day – Queen's Park – Trinidad] - (:unkn) unknown (The Bonanza, Smith Bros and Co., Trinidad, 2010)
This is a vintage postcard showcasing gentlemen and ladies attending "Race Day" at Queen's Park, Trinidad. The sky is bright blue the grass is verdant and green. Men and women are tracking through the grass leaving a beaten muddy path. The men all seem to be wearing black jackets and hats and all the women seem to be wearing full length white dresses. A few of the ladies are sheltering from the sun under red umbrellas. Everyone is walking toward the white barriers at the left edge of the photograph where hordes of people have already gathered to watch the races. There is a building at mid-ground which is probably the race stand and behind it and stretching from left to right is a line of large spreading trees. The tree behind the main building looks like a Samaan tree. The Northern Range looks misty blue. The Queen's Park was also informally called the Savannah, the Grand Savannah and the Queen's Park Savannah.
Colour: Coloured; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Horse racing--Trinidad and Tobago; Pavilions--Trinidad and Tobago; Spectators--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Trees--Trinidad and Tobago; Mountains--Trinidad and Tobago; Savannas--Trinidad and Tobago; [1908]; Buildings--Trinidad and Tobago; Persons--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)